PENGARUH SISTEM PEMBAGIAN JASA MEDIK TERHADAP KEPUASAN KERJA TENAGA KESEHATAN DI UPT PUSKESMAS PANTAI CERMIN - Hutasoit, Romauli; Wasliati, Balqis; Bangun, Sri Melda (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Community Health Centers were the spearhead of health development in Indo-nesia, to increase awareness, willingness, ability to live for everyone so that op-timal public health degrees are realized, which are primarily responsible for im-plementing all health development efforts. The Social Security Administration Agency provides incentives in the form of medical services to health workers. This study aims to analyze the effect of the Medical Services Distribution System on the Job Satisfaction of Health Workers. This study used a qualitative method with a descriptive design. The main informants in this study were 6 health workers who worked at the Pantai Cermin Community Health Centers. The triangulation informants consisted of the treasurer and the head of the Pantai Cermin and Perbaungan Community Health Centers. The technique of checking the validity of the data uses a triangulation technique. The data analysis process used data reduction, data display and conclusion drawing/verification processes. This study found that the majority of health workers were dissatisfied with the system of providing medical services and were dissatisfied with their work in public health centers. There is an influence of the Medical Services Distribution System on the Job Satisfaction of Health Workers. The Community Health Center was expected to be able to provide understanding to health workers regarding the aspects that are assessed in calculating points for the amount of medical services, so that health workers do not only see attendance as a requirement, but also other aspects which include education, length of service and position.